Identification of molecular species of cholesteryl ester hydroperoxides in very low-density and intermediate-density lipoproteins. (November 2014) - Shrestha, Rojeet; Hui, Shu-Ping; Sakurai, Toshihiro; Yagi, Akiko; Takahashi, Yuji; Takeda, Seiji; Jin, Shigeki; Fuda, Hirotoshi; Chiba, Hitoshi
Background: Oxidation of lipoproteins is thought to play a crucial role in atherogenesis. Role for triglyceride-rich lipoproteins in atherogenesis is unclear. Thus, we aimed to investigate whether cholesteryl ester hydroperoxides (CEOOH) are present in very low-density lipoproteins (VLDL) and intermediate-density lipoproteins (IDL) by using highly sensitive liquid chromatography/mass spectrometry. Methods: Total lipids were extracted from the plasma of healthy donors ( n  = 6) and their fractions of VLDL and IDL. Additional three plasma samples were analysed freshly for CEOOH. Detection and identification of CEOOH was conducted by liquid chromatography/LTQ ion trap mass spectrometry/Orbitrap high mass accuracy mass spectrometry. Authentic standards of CEOOH were used for unequivocal identification on the basis of their mass spectra. Results: We identified six molecular CEOOH species overall, namely, Ch18:1-OOH, Ch18:2-OOH, Ch18:3-OOH, Ch20:4-OOH, Ch20:5-OOH and Ch22:6-OOH. Of them, Ch18:2-OOH, Ch20:5-OOH, Ch20:4-OOH and Ch22:6-OOH were detected in all IDL samples, while only Ch20:4-OOH was detected in all VLDL samples. All of CEOOH species except for Ch18:3-OOH were detected in plasma, with constant detection of Ch20:5-OOH, and Ch22:6-OOH in all plasma samples. Conclusion: The presence of CEOOH species in VLDL and IDL was confirmed with the analytical sensitivity of 0.1 pmol, showing the constant appearance of more CEOOH species in IDL than VLDL. This finding might add biochemical evidences of atherogenicity of these lipoproteins. Clinical utility of measuring CEOOH level in these lipoproteins need to be investigated for the risk assessment of the cardiovascular disease.